SPE Reservoir Simulation Symposium 2015
DOI: 10.2118/173268-ms
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-Based Multi-Objective Optimization of On-Off Control Devices Under Geological Uncertainty

Abstract: We consider robust ensemble-based (EnOpt) multi-objective production optimization of on-off inflow control devices (ICDs) for a sector model inspired on a real-field case. The use of on-off valves as optimization variables leads to a discrete control problem. We propose a re-parameterization of such discrete controls in terms of switching times, i.e. we optimize the time at which a particular valve is either open or closed. This transforms the discrete control problem into a continuous control problem which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Most conventional horizontal well design and fracturing optimization methods focus on finding the optimal design parameters to specific metrics, such as estimated ultimate recovery (EUR), cumulative gas production over a while, or net present value (NPV). The economic analysis recommends the decision with maximum NPV (present value of net benefits, or benefits minus costs, over time) or maximum benefit–cost ratio (present value of benefits to present value of fees). The NPV is calculated to obtain the present value of future income generated by eliminating the use of standard economic techniques.…”
Section: Constructing Integrated Optimization Modelmentioning
confidence: 99%
“…Most conventional horizontal well design and fracturing optimization methods focus on finding the optimal design parameters to specific metrics, such as estimated ultimate recovery (EUR), cumulative gas production over a while, or net present value (NPV). The economic analysis recommends the decision with maximum NPV (present value of net benefits, or benefits minus costs, over time) or maximum benefit–cost ratio (present value of benefits to present value of fees). The NPV is calculated to obtain the present value of future income generated by eliminating the use of standard economic techniques.…”
Section: Constructing Integrated Optimization Modelmentioning
confidence: 99%
“…In order to design a production strategy to account for parametric uncertainties in reservoir models, Robust Optimization (RO) has been applied, see Van Essen et al (2009), Chen et al (2012, Yasari et al (2013) and Fonseca et al (2015). In order to design a production strategy to account for parametric uncertainties in reservoir models, Robust Optimization (RO) has been applied, see Van Essen et al (2009), Chen et al (2012, Yasari et al (2013) and Fonseca et al (2015).…”
Section: Robust Optimizationmentioning
confidence: 99%
“…This operation is dependent on many factors, such as well pattern and reservoir characteristics, which may vary over time (Brouwer & Jansen, 2004;Addiego-Guevara et al, 2008;Pinto et al, 2015). Many studies address optimization procedures for ICV operation (Yeten et al, 2004;Sarma et al, 2005;Naus et al, 2006;Dilib et al 2015;Fonseca et al 2015;Chen & Reynolds, 2017;Ilamah & Waterhouse 2018;Aljubran & Horne, 2019), while some authors also reported real case applications (Emerick & Portella, 2007;Van Essen et al, 2009). Botechia et al (2021) and Botechia and Schiozer (2022) proposed and evaluated different model-based methodologies to optimize the operation of ICVs in producers and injectors, respectively, to improve the management and economic return of fields with the aforementioned characteristics.…”
Section: Introductionmentioning
confidence: 99%